How do you use the sum and difference formula to simplify #cos((17pi)/12)#?

4 Answers
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Nghi N. Share
Mar 23, 2017

Answer:

#- sqrt(2 - sqrt3)/2#

Explanation:

#cos((17pi)/12) = cos ((-7pi)/12 + (24pi)/12) = cos ((-7pi)/12 + 2pi) =#
#= cos ((-7pi)/12) = cos ((7pi)/12) = cos (pi/12 + pi/2) = - sin (pi/12)#
Find #sin (pi/12)# by using trig identity:
#2sin^2 (pi/12) = 1 - cos (pi/6) = 1 - sqrt3/2 = (2 - sqrt3)/2#
#sin^2 (pi/12) = (2 - sqrt3)/4#
#sin (pi/12) = +- sqrt(2 - sqrt3)/2#.
Since #sin (pi/12)# is positive, then take the positive value.
#sin (pi/12) = sqrt(2 - sqrt3)/2#
Finally,
#cos ((17pi)/12) = - sin (pi/12) = - sqrt(2 - sqrt3)/2#

Was this helpful? Let the contributor know!
1500
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Nghi N. Share
Mar 3, 2017

Answer:

#- cos ((5pi)/12)#

Explanation:

Simplify -->
#cos ((17pi)/12) = cos ((5pi)/12 + pi) = - cos ((5pi)/12)#

Was this helpful? Let the contributor know!
1500
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1

This answer has been featured!

Featured answers represent the very best answers the Socratic community can create.

Learn more about featured answers

dk_ch Share
Oct 29, 2016

#cos((17pi)/12)#

#cos((24pi-7pi)/12)#

#=cos(2pi-(7pi)/12)#

#=cos((7pi)/12)#

#=cos((4pi+3pi)/12)#

#=cos((4pi)/12+(3pi)/12)#

#=cos(pi/3+pi/4)#

#=cos(pi/3)cos(pi/4)-sin(pi/3)sin(pi/4)#

#=1/2*1/sqrt2-sqrt3/2*1/sqrt2#

#=(1-sqrt3)/(2sqrt2)#

#=1/4(sqrt2-sqrt6)#

Was this helpful? Let the contributor know!
1500
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1

This answer has been featured!

Featured answers represent the very best answers the Socratic community can create.

Learn more about featured answers

Sep 15, 2016

Answer:

#cos((17pi)/12)=(1-sqrt3)/(2sqrt2)#

Explanation:

#cos(A+B)=cosAcosB-sinAsinB#

Let #A=(8pi)/12=2pi/3# and #B=(9pi)/12=(3pi)/4#, then #A+B=(17pi)/12#

Now #cosA=cos((2pi)/3)=cos(pi-pi/3)=-cos(pi/3)=-1/2#;

#sinA=sin((2pi)/3)=sin(pi-pi/3)=sin(pi/3)=sqrt3/2#;

#cosB=cos(3pi)/4=cos(pi-pi/4)=-cospi/4=-1/sqrt2#; and

#sinB=sin((3pi)/4)=sin(pi-pi/4)=sin(pi/4)=1/sqrt2#

Hence, #cos((17pi)/12)=cos(A+B)#

= #cosAcosB-sinAsinB#

= #(-1/2)xx(-1/sqrt2)-(sqrt3/2)xx(1/sqrt2)#

= #1/(2sqrt2)-sqrt3/(2sqrt2)=(1-sqrt3)/(2sqrt2)#

Was this helpful? Let the contributor know!
1500
Add an answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer
Impact of this question
Answer impact map
123 views around the world
You can reuse this answer
Creative Commons License